RELATIONSHIP BETWEEN ACADEMIC ACHIEVEMENT INDEX TOWARD SELF-OBSERVATION AND SELF-JUDGMENT FACTOR SCORES - Rahma Faelasofi; Khoirin Nisa; Mustofa Usman; Tina Yunarti (EMTEKA: Jurnal Pendidikan Matematika, 2026)
Student academic achievement is one indicator in assessing the success of the educational process in higher education. Academic achievement is influenced not only by intellectual ability but also by various psychological factors related to students' self-regulation skills in managing the learning process. One component of self-regulation suspected to be related to academic success is self-observation and self-judgment. However, research specifically examining the relationship between these two constructs and student academic achievement is still limited. Therefore, this study aims to analyze the relationship between student academic achievement and self-observation and self-judgment factor scores. This study uses a quantitative approach with data obtained from students through a questionnaire instrument. The study population was third-semester students at four universities in Lampung Province, with the sampling technique used being cluster random sampling. Prior to the relationship analysis, the self-observation and self-judgment variables were tested using Confirmatory Factor Analysis (CFA). After the model was declared valid and fit by CFA, factor scores were calculated for each respondent. Next, the analysis of the relationship between self-observation and self-judgment factor scores and the Cumulative Grade Point Average (GPA) was conducted using robust regression. The results of the study showed that self-observation had a positive relationship with GPA, while self-judgment showed a negative relationship with GPA. However, both variables did not show a statistically significant effect on GPA. This finding indicates that although self-observation and self-judgment are important parts of self-regulation mechanisms, their contribution to GPA has not been proven significant in this study. This study provides an empirical overview of the relationship between psychological factors in the learning process and students' academic achievement. Prestasi akademik mahasiswa merupakan salah satu indikator dalam menilai keberhasilan proses pendidikan di perguruan tinggi. Pencapaian prestasi akademik tidak hanya dipengaruhi oleh kemampuan intelektual, tetapi juga oleh berbagai faktor psikologis yang berkaitan dengan kemampuan regulasi diri mahasiswa dalam mengelola proses belajar. Salah satu komponen regulasi diri yang diduga memiliki hubungan dengan keberhasilan akademik adalah kemampuan self-observation dan self-judgment. Namun demikian, penelitian yang secara khusus mengkaji hubungan kedua konstruk dengan prestasi akademik mahasiswa masih terbatas. Oleh karena itu, penelitian ini bertujuan untuk menganalisis hubungan prestasi akademik mahasiswa dengan skor faktor self-observation dan self-judgment. Penelitian ini menggunakan pendekatan kuantitatif dengan data yang diperoleh dari mahasiswa melalui instrumen angket. Populasi penelitian ini adalah mahasiswa semester III pada empat perguruan tinggi di Provinsi Lampung, dengan teknik sampling yang digunakan adalah cluster random sampling. Sebelum dilakukan analisis hubungan, variabel self-observation dan self-judgment diuji menggunakan Confirmatory Factor Analysis (CFA). Setelah model dinyatakan valid dan fit dengan CFA, maka dapat dihitung skor faktor untuk setiap responden. Selanjutnya, analisis hubungan antar skor faktor self-observation dan self-judgment terhadap Indeks Prestasi Kumulatif (IPK) dilakukan menggunakan regresi robust. Hasil penelitian menunjukkan bahwa self-observation memiliki hubungan positif terhadap IPK, sedangkan self-judgment menunjukkan hubungan negatif terhadap IPK. Namun, kedua variabel tidak menunjukkan pengaruh yang signifikan secara statistik terhadap IPK. Temuan ini mengindikasikan bahwa meskipun kemampuan self-observation dan self-judgment merupakan bagian penting dari mekanisme regulasi diri, kontribusi terhadap IPK dalam penelitian ini belum terbukti secara signifikan. Penelitian ini memberikan gambaran empiris mengenai hubungan antara faktor psikologis dalam proses belajar dengan capaian akademik mahasiswa